The Role of Social Capital in Serangan Sub-District, Denpasar-Bali - Nugraha, I Gede Putra; Antara, I Made; Budiarsa, Made; Paturusi, Syamsul Alam (E-Journal of Tourism, 2021)
Serangan sub-district as a potential area is a representation of Denpasar City Government’s policy on environmental conservation, historical and cultural values, the interests of the world of education, and the interests of cultural tourism full of attractions. The purpose of this study is to identify the role of social capital in the development of sustainable tourism in the Serangan Sub-District and to analyze the effect of government roles, community participation, and social capital on destination quality and sustainable tourism development in the Serangan sub-district. The result of this research shows that social capital norms in the Serangan sub-district has an important role in tourism development in the Serangan sub-district, where the norms in traditional villages in the Serangan sub-district are still very strong.